From “Global Village” to “Blackbox Society”? Digital identities and political communication in the age of surveillance capitalism - Strauß, Stefan (Momentum Quarterly, 2020)
Digitization and social media have been changing political (mass-)communication significantly. The Cambridge Analytica data scandal underlines the strong ambivalence between political empowerment and polarization. Problems of filter bubbles, “fake news”, disinformation etc. increasingly challenge free political will formation and democracy. This paper explores how and why social media altered political communication in this respect and what role the toolbox of surveillance capitalism plays here. In the light of a structural transformation of the public it discusses how digital mass communication functions with the dynamics of social media. Based on the case of the Cambridge Analytica scandal, the paper reveals how digital identification practices, microtargeting and modern forms of persuasion marketing serve to create political impact by influencing political opinions and how this relates to mechanisms of propaganda. Finally, the paper argues for stricter regulation of political online communication and digital campaigning to counter populism.